2006
DOI: 10.1124/dmd.106.010363
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and in Vitro Characterization of Chlorzoxazone Metabolism and Hepatic CYP2E1 Levels in African Green Monkeys: Induction by Chronic Nicotine Treatment

Abstract: ABSTRACT:CYP2E1 metabolizes compounds, including clinical drugs, organic solvents, and tobacco-specific carcinogens. Chlorzoxazone (CZN) is a probe drug used to phenotype for CYP2E1 activity. Smokers have increased CZN clearance during smoking compared with nonsmoking periods; however, it is unclear which cigarette smoke component is causing the increased activity. The relationships between in vivo CZN disposition, in vitro CZN metabolism, and hepatic CYP2E1 have not been investigated in a within-animal design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 38 publications
(62 reference statements)
1
16
0
Order By: Relevance
“…Also, a study with 21-day nicotine dosing in African green monkeys demonstrated the induction of hepatic CYP2E1 protein and activity, including increased chlorzoxazone metabolism in vivo [33]. Moreover, nicotine treatment increased markedly CYP2E1 protein as studied with immunocytochemistry in a human neuroblastoma cell line IMR-32 [16].…”
Section: Discussionmentioning
confidence: 99%
“…Also, a study with 21-day nicotine dosing in African green monkeys demonstrated the induction of hepatic CYP2E1 protein and activity, including increased chlorzoxazone metabolism in vivo [33]. Moreover, nicotine treatment increased markedly CYP2E1 protein as studied with immunocytochemistry in a human neuroblastoma cell line IMR-32 [16].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma CZN levels were assayed on the basis of the methods in Lee et al (2006b). In brief, plasma was centrifuged at 3000g for 10 min, after which 100 l of the supernatant was removed and incubated with ␤-glucuronidase (10 mg/ml, 50 l) overnight at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Ethanol is an inducer of hepatic CYP2E1 protein and activity in humans and monkeys (Lieber, 1997;Ivester et al, 2007). Smoking increases CYP2E1 activity in humans (Benowitz et al, 2003), and chronic nicotine treatment increases hepatic CYP2E1 protein levels and activity in monkeys (Lee et al, 2006b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations